Development of the Russian socio-economic system: challenges and prospects - Kiselev A. A., Soldatova L. I., Shmidt I. I., Fadeeva G. V., Boboshko A. A., Kharlanov A. S., Lapshin V. I., Beketova O. N., Sedov I. D., Bagirova A. R., Loseva E. S., Fedorova I. A., Dashian S. G., Fedulova E. A., Burtseva E. V., Medvedeva S. V., Ivaniuzhenko A. B., Shchankina L. N., Voronenko E. A., Piatitskaia D. V., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Lavina T. A., Gritsevich T. I., Russova N. V., Zakharova A. N., Paevskaia S. L., Mironova N. G. (Development of the Russian socio-economic system: challenges and prospects, 2024)
the authors consider the model of the Russian economy during its transition to a mobilization regime. To unlock the potential of China's nanoclusters as a global ICT leader and leading US-Chinese decoupling in the development of Industry 4.0 and the growth of key competencies in digitalization and the efficiency of the national economy.
Keywords: Китай; Россия; США; China; Russia; USA; localization; глокализация; СВО; фрагментация; альтерглобализация; дикаплинг; мобилизационная экономика; нанокластер; decoupling; OWN; mobilization economy; nanocluster; fragmentation; alterglobalization